Co-occurrence of autistic and schizotypal traits and its association with emotional and psychosocial function in Chinese college students. (February 2017) - Shi, Li-juan; Liu, Wen-hua; Shi, Hai-song; Yan, Chao; Wang, Ya; Wang, Yi; Cheung, Eric F.C.; Chan, Raymond C.K.
Abstract: Empirical findings suggest an overlap between autism spectrum disorders (ASD) and schizophrenia spectrum disorders (SSD). Co-occurring autistic and positive schizotypal traits may have a moderating effect on behaviour and cognition. This study attempted to examine the co-occurrence rate of autistic and schizotypal traits in otherwise healthy college students and to test the moderating effect of co-occurring autistic and schizotypal traits on executive function, emotion processing and social function. Eight hundred and sixty-four participants took part in the present study. The results showed that the co-occurrence rate of autistic and schizotypal trait was 3.4% at baseline and 2.4% at one-year follow-up. The interaction between autistic traits and schizotypal traits was associated with better executive functioning and social functioning but poorer emotional expression. Highlights: The co-occurrence rate of autistic and schizotypal trait was 3.4% at baseline and 2.4% at one year follow-up. The interaction between autistic traits and schizotypal traits was associated with better executive functioning and social functioning but poorer emotional expression.